Electrical structure of Gulu geothermal field in Southern Tibet and its implication for the high-temperature geothermal system - Wan, Hanping; Wang, Qiao (Frontiers in Earth Science, 2023)
The Yadong-Gulu rift (YGR) South Tibet is a Cenozoic active rift, which is endowed with abundant geothermal resources. The Gulu geothermal field (GGF) is located in the Northern section of the rift, where a large number of high-temperature hot springs develop, but its geothermal system is mysterious. In this study, the three-dimensional (3D) electrical structure of GGF is revealed by broad magnetotelluric (MT) and audio magnetotelluric (AMT). MT reveals that middle and upper crust conductors are developed in the subsurface of GGF. The conductors may originate from the partial melting that drives the geothermal system. AMT reveals that the electrical structure of GGF is conductive alternation cap overlying more resistive reservoir, which is consistent with the classical electrical structure of geothermal systems in worldwide active tectonic zones. According to the geothermal system model, cold fluids may converge from the periphery of GGF to the middle, wherein fault F1 (the Western branch of Jiulazi-Sanxung fault) may be the main channel for cold fluids to migrate downward. The fluids are heated by partial melting in the middle and upper crust, and may migrate upward along fault F2 (the middle branch of Jiulazi-Sanxung fault) and develop into heat reservoirs.